ANALISIS FUNGSI MAJELIS PERMUSYAWARATAN RAKYAT (MPR) DALAM HIERARKI PERUNDANG-UNDANGAN - Kevin Andreas Halomoan Tambunan; Ridha Nababan; Rimma Anisa Siagian; Roslin Naiborhu; Putri Paulina Sembiring (STKIP Subang, 2024)
The role of the People's Consultative Assembly (MPR) in the Indonesian constitutional system as well as the hierarchy of laws and regulations in Indonesia is discussed in this report. The legal sequence system known as the